THE RESEARCH ABOUT ANTIOXIDANT ACTIVITY OF PEPTIDES OBTAINED FROM JERUSALEM ARTICHOKE PROTEINS - Firuza Rustambekova; Khasanov Khasan (International Journal of Innovations in Engineering Research and Technology, 2021)
In this work, the antioxidant activity of peptides obtained from Jerusalem artichoke proteins using acidic and neutral pretenses was studied. It was seen that products with prophylactic properties, received using the latest technology from local varieties of Jerusalem artichoke, determine the high antioxidant activity of peptides of protein origin. The obtained proteins can be applied as a source for the production of antioxidant peptides.